Self-Awareness dalam Perilaku Etis Profesi Akuntansi: Bibliometric Literature Review - Gandini, Aulia; Kurniawati, Ervinda Dwi; Suhartini, Dwi (Nominal: Barometer Riset Akuntansi dan Manajemen, 2024)
ABSTRACTThe aim of this research is to analyze the concept of self-awareness and ethical behavior in supporting the accounting profession. This study uses bibliometric analysis techniques on 125 articles selected from Google Scholar in the 2018-2023 period, with the help of Publish or Perish (PoP), VOSviewer, and Mendeley software. The research results show that self-awareness not only contributes to the development of ethical behavior but also significantly influences audit quality and interpersonal relationships in the accounting work environment. Self-awareness has been proven to play an important role in helping accountants maintain integrity, objectivity, competence, confidentiality and professional behavior, which are key elements of an accountant's code of ethics. Bibliometric analysis reveals that articles examining self-awareness in the context of accounting ethics tend to emphasize the importance of this component in improving ethical decision making and conflict management in accounting practice. The contribution of this research shows that to achieve more ethical accounting practices, a holistic approach is needed that integrates self-awareness with existing ethical standards.Keywords: Self-awareness, Ethical Behavior, Accounting Profession, Bibliometric AnalysisABSTRAKTujuan penelitian ini adalah untuk menganalisis konsep self-awareness dan perilaku etis dalam menunjang profesi akuntansi. Studi ini menggunakan teknik analisis bibliometrik terhadap 125 artikel yang dipilih dari Google Scholar dalam rentang waktu 2018-2023, dengan bantuan perangkat lunak Publish or Perish (PoP), VOSviewer, dan Mendeley. Hasil penelitian menunjukkan bahwa self-awareness tidak hanya berkontribusi pada pengembangan perilaku etis tetapi juga secara signifikan mempengaruhi kualitas audit dan hubungan interpersonal dalam lingkungan kerja akuntansi. Self-awareness terbukti berperan penting dalam membantu akuntan mempertahankan integritas, objektivitas, kompetensi, kerahasiaan, dan perilaku profesional, yang merupakan elemen kunci dari kode etik akuntan. Analisis bibliometrik mengungkapkan bahwa artikel yang mengkaji self-awareness dalam konteks etika akuntansi cenderung menekankan pentingnya komponen ini dalam meningkatkan pengambilan keputusan etis dan pengelolaan konflik dalam praktik akuntansi. Kontribusi penelitian ini menunjukkan bahwa untuk mencapai praktik akuntansi yang lebih beretika, diperlukan pendekatan holistik yang mengintegrasikan self-awareness dengan standar etika yang ada.Kata kunci: Self-awareness, Perilaku Etis, Profesi Akuntansi, Analisis Bibliometrik